Accessing Aswesuma: Key findings on Sri Lanka’s new social protection program from the bright 2024-25 national survey - Hülsen, Vivien; Klas, Nicolas; Headey, Derek D.; Munasinghe, Dilusha; Ranucci, Immacolata; Sabai, Moe; van Asselt, Joanna; Weerasinghe, Krishani (International Food Policy Research Institute, 2025)
• We use the nationally representative BRIGHT 2024-25 survey to document Aswesuma access at the national and subnational level, and among poor and food-insecure households • At the time of the BRIGHT 2024-2025 survey, the Aswesuma program covered 29.1% of the Sri Lankan population compared to just 18.8% of the population under Samurdhi in 2016: a 10.3 percentage point improvement. However, at the time of the survey, the Aswesuma program has still not reached its target of 35% national population coverage. • Encouragingly, the largest expansion of cash transfer access was in upland (Estate) districts, who had limited access to cash transfers under the previous Samurdhi program • Aswesuma access among poor populations was highest in the Estate sector (56%), followed by the rural (46%) and urban populations (44%) • Aswesuma transfers are unlikely to reduce employment or other income-generating activities among the poor, as Aswesuma cash transfers only represent 19% of the expenditures of the poorest 20% of households, and just 10% for the next poorest group. • While Aswesuma transfers may protect households against low calorie intake (hunger), Aswesuma households still have low-quality diets, under-consuming fruits, vegetables, dairy, and legumes in particular • Nutritional knowledge is also much poorer among Aswesuma beneficiaries than the rest of the Sri Lankan population, particularly knowledge of key micronutrient-rich foods • These results imply the need for a wide range of policy-oriented research and follow-up surveys on drivers of access to Aswesuma, but also impacts of Aswesuma on key welfare indicators • There is also a need to explore and improve multisectoral coordination between Aswesuma and other programs on child nutrition and development, as well as women’s empowerment.